Dealing with Identity Loss and Well-being of Unemployed Young People (Journal of Advanced Research in Social Sciences, 2019)
The research aims to study the relationship between the status of unemployment and the social identity and well-being of young people. We conducted a quantitative survey with 110 unemployed young people; In-depth interviews were conducted with 24 participants. Findings show that the experience of unemployment is negative. It causes financial problems, nurtures a feeling of dependence, negative social identity; it is also linked to reduced opportunities for social and cultural involvement. The attitude of society towards unemployed differs according to what unemployment is attributed to. It is more positive when it is assigned to the economic situation in the country and hence to a lack of jobs, but is more harmful when it is attributed to a lack of motivation or qualification of a person. To escape from the negative social identity unemployed young people trying social mobility. The long-term unemployed are more active than the short-term unemployed. Unemployment affects well-being. Unemployed youth is less than the general population satisfied with their life although they have a similar level of self-esteem.